Perubahan Sosial: Respons Masyarakat Pringkuku terhadap Implementasi Program Urusan Sosial - Sumardi Sumardi; Dian Tias Aorta (Lembaga Yasin AlSys, 2026)
This study was motivated by differences in community responses to the implementation of the Social Affairs Program in Pringkuku Subdistrict, which reflect the dynamics of social change as well as the gap between policy and field realities. This study aims to analyze community responses to the implementation of the Social Affairs Program in Pringkuku Village, Pringkuku Subdistrict, Pacitan Regency. This study used a qualitative approach with a descriptive-analytical type. Data were collected through in-depth interviews, participatory observation, and documentation, with informants selected purposively, including village officials, community leaders, and program beneficiaries. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing and verification. The results showed that community responses to the implementation of the social affairs program were diverse and were influenced by the level of public understanding of the program, the role of local leaders, and the suitability of the program to the needs and social values of the local community. In addition, the level of community participation in program planning, implementation, utilization of results, and evaluation became an important factor in determining the effectiveness of the implementation of the social policy. The conclusion of this study confirms that social programs at the village level should not be oriented only toward the provision of assistance, but must also be directed toward enhancing community capacity so that people can become economically and socially self-reliant. These findings contribute to strengthening the study of social policy, social change, and community participation, and confirm that the success of program implementation is strongly determined by the active involvement of the community in all stages of implementation.